1995
DOI: 10.1007/bf02246112
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine serum levels and side effects during steady state treatment of schizophrenic patients: a cross-sectional study

Abstract: Serum clozapine (S-Cloza) and serum desmethyl-clozapine concentrations (S-Descloza) were measured in 30 chronic schizophrenic in- and out-patients on a variable dose regimen. All patients were in steady state with respect to clozapine therapy and in a stable condition with respect to psychotic illness. The 24-h clozapine dose (median with interquartile range in parenthesis) was 350 (228-425) mg/24 h (range 100-700). There was a weak positive correlation between doses and the BPRS total score (r = 0.44, P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 24 publications
3
46
0
3
Order By: Relevance
“…Nonetheless, these values are within the range of NDMC plasma concentrations (175-435 ng/ml; 0.6-1.4 mM) measured in schizophrenics following chronic treatment with clozapine (Centorrino et al, 1994;Olesen et al, 1995;Aravagiri and Marder, 2001;Frazier et al, 2003). The concentrations reached by NDMC in the human brain under these conditions are unknown.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Nonetheless, these values are within the range of NDMC plasma concentrations (175-435 ng/ml; 0.6-1.4 mM) measured in schizophrenics following chronic treatment with clozapine (Centorrino et al, 1994;Olesen et al, 1995;Aravagiri and Marder, 2001;Frazier et al, 2003). The concentrations reached by NDMC in the human brain under these conditions are unknown.…”
Section: Discussionmentioning
confidence: 54%
“…Whereas CNOX can be rapidly re-converted to clozapine, NDMC reaches considerable plasma concentrations ranging from 49 to 140% of those of the parent compound in schizophrenic patients (Centorrino et al, 1994;Olesen et al, 1995;Aravagiri and Marder, 2001;Frazier et al, 2003) and from 50 to 220% in the rat (Baldessarini et al, 1993;Weigmann et al, 1999). In the rat brain, concentrations of NDMC higher than those in serum have been detected following clozapine administration, indicating that the metabolite can cross the blood-brain barrier (Weigmann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a relationship between serum clozapine concentrations and CNS adverse effects. For example, Olesen et al (31) found a significant correlation between clozapine concentrations and EEG changes. Concentrations above 1000 ng mL -1 significantly increased the risk of confusion, delirium and generalized seizures (31,32).…”
Section: Tdm Of Particular Atypical Antipsychotic Drugsmentioning
confidence: 99%
“…In addition, the average ratio between norclozapine and clozapine is 0.59, [49][50][51][52][53][54][55] resulting in a norclozapine concentration of 106 nM in the spinal fluid. However, because norclozapine has a dissociation constant of 100 nM at D2, compared to a value of 44 nM for clozapine (Table 1), the spinal fluid concentration of 106 nM norclozapine is equivalent to a 'clozapine-like D2-blocking concentration' of 106 nM × 44 nM/100 nM or 47 nM.…”
Section: Figurementioning
confidence: 99%